(untitled) (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
This article explores the causal relationship between freedom, the imagined (perfection), and the observed design in nature (diversity). The presentation is with familiar examples of perfection and diversity over space and in time: the configurations and rhythms of moving and changing designs of people, animals, athletes, technologies, universities, and science itself: divergent evolution hand-in-glove with convergent evolution.